The effects of noradrenergic re-uptake inhibition on memory encoding in man. - Papps, B; Shajahan, P; Ebmeier, K; O'Carroll, R (2002)
RATIONALE: Animal and human evidence implicate the central noradrenergic system in the process of memory modulation for emotional material. Blockade of the beta-adrenergic system in humans has been shown to result in decreased recall and recognition memory performance, relative to placebo, for the emotional elements of a series of slides accompanied by a narrative. Stimulation of the noradrenergic system with yohimbine has also been shown to result in increased recall and recognition performance relative to placebo for the same stimulus materials. OBJECTIVES: The present study tested the hypothesis that stimulating the central noradrenergic system using the new noradrenaline re-uptake inhibitor reboxetine would result in a dose-dependent enhancement of memory for emotional material in man. METHODS: The central noradrenergic system was manipulated using reboxetine in a double-blind, randomised between-group, placebo-controlled design with 36 healthy adult subjects in each of three groups (placebo, 4 and 8 mg reboxetine). Free recall and recognition memory performance were assessed in a 'surprise' memory test following a 7-day interval. RESULTS: We found no memory enhancing effect of reboxetine. In contrast we observed a dose-dependent effect on memory opposite to the predicted direction. There were no significant differences between groups in self-rated stress and arousal scores or self-rated emotional reactions to the stimuli. All groups showed the expected increased memory performance for the middle 'emotive' phase of the story. CONCLUSION: Selective stimulation of the central noradrenergic system at encoding did not result in enhanced long-term memory for emotional material in man.